The Use of Explicitation to Retain the Foreignness of Olga Tokarczuk’s Flights - Marcelina Pietryga (Ksiegarnia Akademicka Publishing, 2021)
This article discusses the topic of explicitation applied as a measure of retaining foreignness in the English translation of Flights. It has been observed that the main types of explicitation used in the analysed novel are either explanations of the context which may be lost in the English translation or presentation of both, the problematic Polish words and their English explanation. The analysis has confirmed that explicitation gives the possibly to preserve almost exact level of foreignness as in the case of the source text. The second shift analysed in this study is implicitation, applied in a situation when retaining foreignness was not possible. This phenomenon has been implemented as a response to information explicitly stated in the source text. However, this measure does not negatively influence the TT, but on the contrary, it helps to provide a consistent and understandable text.